Developing a shariah-compliant equity-based crowdfunding model towards a Malaysian low-carbon consumer society - Rafia, Afroz; Tudin, Rabaah; Morshed, Niaz; Duasa, Jarita (University Malaya, 2019)
Malaysian households’ energy consumption increased by 6.9%. Meanwhile, energy supply increased by 6.1% from 1991 to 2006. If energy consumption continues to increase, it will put significant strain on the energy supply. The steady growth of electricity consumption in Malaysia is directly linked to CO2 emissions and climate change, which directly increases annual temperature and temperature-related health problems. The development of a low-carbon society is important as Malaysia is experiencing increasing CO2 emissions. A low-carbon society aims to reduce CO2 and improve life. The use of PV solar energy can be an effective solution, but Malaysian households face several barriers to using solar energy in their homes, such as high price, lack of physical and financial means, in addition to a lack of awareness and social support. This study proposes a model that will benefit from PV solar panels with Shariah-compliant equity-based crowd financing. In this study, electricity usage and energy usage of households, their interest in solar energy and the obstacles they encounter in the use of solar energy are discussed. A total of 260 participants from Kuala Lumpur were surveyed. The majority of respondents (74%) claimed that electricity usage was between 0-3000 KWh. The findings of this study show that high initial costs, limited knowledge of renewable energy technologies, lack of the best possible price, and lack of awareness are the biggest obstacles to sustainable renewable energy development. Besides, 47% of respondents were willing to accept the proposed model to help them in using solar energy in their homes. Furthermore, a logit model was estimated to investigate the factors that may affect the willingness of the households to accept the model. The results of the logit model reveal that income, household size and knowledge about climate change affect significantly and positively the willingness of the households to accept the model. This study suggests that the government can take the initiative to raise awareness of the households about the need for renewable energy and low-carbon consumer society.